2014
DOI: 10.1016/s2213-2600(14)70100-6
|View full text |Cite
|
Sign up to set email alerts
|

Ataluren for the treatment of nonsense-mutation cystic fibrosis: a randomised, double-blind, placebo-controlled phase 3 trial

Abstract: Background Ataluren was developed to restore functional protein production in genetic disorders caused by nonsense mutations, which are the cause of cystic fibrosis (CF) in 10% of patients.. Methods This randomized, double-blind, placebo-controlled study enrolled 238 patients ≥6 years with nmCF to receive oral ataluren 10 mg/kg in the morning, 10 mg/kg mid-day, and 20 mg/kg in the evening or matching placebo for 48 weeks. The primary endpoint was relative change in % predicted forced expiratory volume in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
235
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(248 citation statements)
references
References 28 publications
5
235
1
5
Order By: Relevance
“…However, in cells manifesting substantial ataluren-mediated readthrough of the PTC-containing NanoLuc mRNA, addition of tobramycin showed strong, dose-dependent reduction of ataluren's readthrough activity (Fig. 4), consistent with previous work showing that aminoglycosides reduce the ability of ataluren to promote readthrough but nonaminoglycoside antibiotics have no effect (12). Quantitation of this effect indicated that tobramycin inhibition of ataluren's activity had an IC 50 of 20 μM (Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…However, in cells manifesting substantial ataluren-mediated readthrough of the PTC-containing NanoLuc mRNA, addition of tobramycin showed strong, dose-dependent reduction of ataluren's readthrough activity (Fig. 4), consistent with previous work showing that aminoglycosides reduce the ability of ataluren to promote readthrough but nonaminoglycoside antibiotics have no effect (12). Quantitation of this effect indicated that tobramycin inhibition of ataluren's activity had an IC 50 of 20 μM (Fig.…”
Section: Resultssupporting
confidence: 88%
“…1 and SI Appendix, Fig. S3) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)23); (ii) the effects on luciferase activity could not be independently replicated by others (24) or by us (SI Appendix , Fig. S3C); (iii) ataluren's putative luciferase inhibitory activity depends on a specific enzyme substrate (25); and (iv) most of the hypothetical inhibitory molecule, PTC124-AMP (22), is rapidly converted to the active readthrough molecule PTC124 (ataluren) under conditions of in vitro translation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No statistically significant difference was seen in the ataluren treatment group when compared to the placebo group in a large phase 3 trial, although significant benefits were seen in patients not receiving inhaled aminoglycoside antibiotics; these drugs also act on the ribosome, making competitive inhibition highly likely as the explanation (15). A second phase 3 trial is currently underway in patients 6 years and older not receiving these drugs (NCT02139306) .Read through agents also have therapeutic potential for a range of other inherited diseases caused by stop mutations; conditional approval has recently been granted for certain types of Duchenne muscular dystrophy.…”
Section: Read-through Agentsmentioning
confidence: 98%